Examining How Rituals Reinforce Organizational Culture within Gen Z Learning Community - Sutarjo, Moch. Armien Syifaa; Wisudawaty, Hanna; Fariza, Muhammad Rio (Jurnal Dinamika Ilmu Komunikasi, 2025)
This study examines how organizational rituals reinforce culture and identity within a Gen Z–based educational community. Using a descriptive qualitative approach, data were gathered through interviews, participant observation, and document analysis in the Troopers community of Armidale English College (AEC), Bandung, Indonesia. Five participants of different seniority levels were purposively selected to represent varied cultural experiences. The findings show that rituals perform four main functions: (1) onboarding and identity building, where initiation activities convey core organizational values; (2) institutional learning, as meetings and peer-led programs serve as platforms for experiential training; (3) social cohesion, where informal rituals like sports and casual gatherings foster trust and solidarity; and (4) collective identity formation, expressed through shared symbols such as uniforms and chants. These practices combine formal and spontaneous elements, linking classical views of organizational culture (Schein, 2010; Goffman, 1967) with Gen Z’s emphasis on authenticity and collaboration. The study contributes theoretically by framing rituals as communicative strategies that sustain organizational culture in youth-oriented learning environments. Practically, it provides insights for educational and volunteer organizations to design culturally relevant engagement strategies that enhance communication, loyalty, and identity formation in the post-pandemic context.